Environment modification at school to promote physical activity among adolescents: a cluster randomized controlled trial - Raycauan Silva Benthroldo; Vitor Barreto Paravidino; Diana Barbosa Cunha; Mauro Felippe Felix Mediano; Rosely Sichieri; Emanuele Souza Marques (Associação Brasileira de Pós-Graduação em Saúde Coletiva, 2022)
ABSTRACT: Objective: To assess the effect of modifications of the school environment on physical activity in Brazilian adolescent students. Methods: Seven public schools in Duque de Caxias (Brazil) were randomized into control and intervention groups. The intervention group underwent modifications in the school environment (painting of hopscotch and school courts) and the provision of sports equipment (balls, basketball table, soccer goalpost, volleyball nets, and others) to stimulate physical activity. Additionally, footsteps towards the court and materials were painted, and a superhero character called Super Active was introduced. Total physical activity was measured using a validated questionnaire for adolescents. Generalized linear models were used to evaluate the effect of the intervention, adjusted by sex. Results: The sample consisted of 975 adolescents, with a mean age of 11.52 years (standard deviation - SD 1.43), and 56.7% were boys. After the one-month intervention, both groups' total physical activity time increased. The estimated changes from baseline were not different between the intervention and control groups (Δ=102.75 and Δ=99.76, respectively; p=0.52). Conclusion: The painting, supply of equipment and other strategies to encourage physical activity in the school environment did not promote a positive effect on improving physical activity among adolescents. Future research is necessary to evaluate the effect of the intervention in the long-term period, particularly in other population contexts in middle-income countries.